2021
DOI: 10.1073/pnas.2100094118
|View full text |Cite
|
Sign up to set email alerts
|

Bright daytime light enhances circadian amplitude in a diurnal mammal

Abstract: Mammalian circadian rhythms are orchestrated by a master pacemaker in the hypothalamic suprachiasmatic nuclei (SCN), which receives information about the 24 h light–dark cycle from the retina. The accepted function of this light signal is to reset circadian phase in order to ensure appropriate synchronization with the celestial day. Here, we ask whether light also impacts another key property of the circadian oscillation, its amplitude. To this end, we measured circadian rhythms in behavioral activity, body te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 69 publications
3
32
0
Order By: Relevance
“…Recordings were performed at room temperature (~ 23°C). A portion of the data appearing in this study also contributed to the investigation of the impact of daytime light intensity on the neurophysiological activity and circadian amplitude in the R. pumilio SCN ( Bano-Otalora et al, 2021 ).…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Recordings were performed at room temperature (~ 23°C). A portion of the data appearing in this study also contributed to the investigation of the impact of daytime light intensity on the neurophysiological activity and circadian amplitude in the R. pumilio SCN ( Bano-Otalora et al, 2021 ).…”
Section: Methodsmentioning
confidence: 94%
“…In summary, our whole-cell recordings and computational modeling highlight the potential importance of I A and cellular membrane resistance in tuning excitability in the R. pumilio SCN. This may be an important step in accommodating SCN activity to diurnal living while maintaining the high day/night contrast in electrical activity (RMP and firing rate) necessary to sustain the robustness of the clock, a contributing factor to promote health and wellbeing ( Ramkisoensing and Meijer, 2015 ; Bano-Otalora et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the genetic models, circadian misalignment caused by environmental/behavioral changes also contributed to glucose metabolism disorders in animal and human research [ 69 ]. The environmental changes often referred to altered light/dark (LD) cycles, and both the time/period and intensity of light would exert a significant effect on circadian rhythms as the SCN receives light signals [ 70 , 71 ]. Nankivell et al reported that short photoperiod exposure led to impaired glucose tolerance in Psammomys obesus [ 72 ].…”
Section: T2dm and Circadian Disruptionmentioning
confidence: 99%